How TV sponsorship can help television spot advertising. (15th January 2019) - Bellman, Steven; Murphy, Jamie; Arismendez, Shruthi Vale; Varan, Duane
Abstract : Purpose: This paper aims to test TV sponsorship bumper effects, for the same brand, on 30-s TV spot advertising. Design/methodology/approach: An experimental study tests sponsorship bumpers and 30-s TV spot ads for eight brands, four familiar and four unfamiliar, using realistic stimuli and a sample representative of the US population. Findings: Sponsorship boosts ad effectiveness and is measured by ad awareness and ad liking. Both effects were stronger for unfamiliar brands. Research limitations/implications: The results show that combining sponsorship with spot advertising has an additive effect. The study design did not allow tests for potential synergy (multiplicative) effects. Practical implications: Advertisers can use the results to evaluate investing in sponsorship and advertising packages, which can help unfamiliar brands achieve familiar brand awareness. Originality/value: To the authors' knowledge, this is the first study to compare the effectiveness of sponsorship-boosted ads with sponsorship bumpers alone and with TV spot ads.